2021
DOI: 10.3390/ijerph18031176
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Crash Characteristics in Shenzhen, China from 2014 to 2016

Abstract: Road traffic crashes cause fatalities and injuries of both drivers/passengers in vehicles and pedestrians outside, thus challenge public health especially in big cities in developing countries like China. Previous efforts mainly focus on a specific crash type or causation to examine the crash characteristics in China while lacking the characteristics of various crash types, factors, and the interplay between them. This study investigated the crash characteristics in Shenzhen, one of the biggest four cities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…7 However, another study on traffic crashes in China found lower correlation of road crashes with rainy weather, which they attributed to a possible tendency of drivers to be more careful during bad weathers. 17 According to this study, the median length of hospital stay for women is 5 days. The length of hospital stay usually corresponds to the severity of injuries sustained, but a study by Cullen et al ( 2021) 18 observed no difference in the severity of injuries sustained between men and women.…”
Section: Discussionmentioning
confidence: 83%
“…7 However, another study on traffic crashes in China found lower correlation of road crashes with rainy weather, which they attributed to a possible tendency of drivers to be more careful during bad weathers. 17 According to this study, the median length of hospital stay for women is 5 days. The length of hospital stay usually corresponds to the severity of injuries sustained, but a study by Cullen et al ( 2021) 18 observed no difference in the severity of injuries sustained between men and women.…”
Section: Discussionmentioning
confidence: 83%
“…There were several reasons why accidents often happen in the morning. For example, high movement of motor vehicles, because there is more activity in the morning [19]. Majority of Indonesian people start their activities in the morning such as going to work or going to school.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the drivers in crashes that took place on rainy days were in many cases young drivers or old drivers. Likewise, Li et al [20] studied the relationship between land-use patterns and vehicle crashes. However, this method does not provide a full understanding of driving behavior [21].…”
Section: Related Workmentioning
confidence: 99%